DEVELOPMENT OF STUDENT WORKSHEET SCIENCE LITERACY IN XI GRADE ON CHEMICAL EQUILIBRIUM TOPIC (UNESA Journal of Chemical Education, 2018)
Student Activity Sheet (LKS) developed in this study based on science literacy on chemical equilibrium material. This study aimed to describe the feasibility of LKS based on validity (content and construct), practicality (student response) and effectiveness (science literacy test result). This type of research uses research and development (R & D) development methods only until the limited trial stage. Data sources were obtained from chemistry lecturer, chemistry subject teacher and 15 students of XI MIA 5 SMA Negeri 7 Surabaya. LKS developed is feasible to be used as teaching materials indicated that the fulfillment of eligibility requirements are: (1) validity consisting of content validity and construct validity to get percentage of each 77,5% and 78,7% with valid category. (2) the practicality of obtaining a percentage of 91.2% with very practical category. (3) the effectiveness underestimated from the postest result gets an average grade of 83.4 with the complete category. The classical increase in the individual as many as 11 students has increased in the "moderate" category and 4 students in the "high" category. Keywords: Worksheet, science literacy, chemical equilibrium